Preparation method of zirconium hydride surface composite hydrogen-resistant coating

By spraying aluminum powder and aluminum oxide powder on the surface of zirconium hydride, forming a zinc-aluminum layered double hydroxide coating through in-situ hydrothermal reaction, and then recombining it with graphene oxide, the problem of hydrogen precipitation of zirconium hydride at working temperature is solved, and a composite hydrogen-retardant coating with significant hydrogen resistance effect and good corrosion resistance is formed, extending the service life of zirconium hydride.

CN119913499APending Publication Date: 2025-05-02ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510102014.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Zirconium hydride has hydrogen precipitation problems within the operating temperature range, which reduces the neutron slowing efficiency and service life.

Method used

A low-pressure air-cooled spraying system is used to spray aluminum powder and aluminum oxide powder on the surface of the zirconium hydride matrix to form an aluminum coating, and a zinc-aluminum layered double hydroxide coating is formed through in-situ hydrothermal reaction, and then electrostatic adsorption and recombination with graphene oxide to form a zinc-aluminum layered double hydroxide-graphene oxide composite hydrogen resistance coating.

Benefits of technology

The composite hydrogen-resistance coating formed by this method has good continuity, complete surface, smoothness, good density and obvious hydrogen-resistance effect. It can effectively extend the service life of the zirconium hydride slower agent and improve corrosion resistance and friction resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913499A_ABST
    Figure CN119913499A_ABST
Patent Text Reader

Abstract

The preparation method of the zirconium hydride surface composite hydrogen-resistant coating disclosed by the embodiment of the invention comprises the following steps: S1, spraying aluminum powder and aluminum oxide powder on the surface of a zirconium hydride matrix in a low-pressure cold gas spraying manner to form an aluminum coating; wherein the particle size of the aluminum powder is 35-45 microns, the particle size of the aluminum oxide powder is 40-50 microns, and the purities of the aluminum powder and the aluminum oxide powder are both greater than 99%; s2, the aluminum coating on the surface of the zirconium hydride matrix and a Zn (NO3) 2.6 H2O solution are subjected to an in-situ hydrothermal reaction, and a zinc-aluminum layered double hydroxide coating is formed through in-situ growth; and S3, compounding the zinc-aluminum layered double hydroxide coating on the surface of the zirconium hydride matrix with graphene oxide in an electrostatic adsorption manner, and forming the zinc-aluminum layered double hydroxide-graphene oxide composite hydrogen-resistant coating on the surface of the zirconium hydride matrix. After the zinc-aluminum layered double hydroxide is treated by electrostatic adsorption of graphene oxide, surface defects are repaired, the zinc-aluminum layered double hydroxide-graphene oxide composite coating is obtained, and the coating is good in continuity, complete and smooth in surface, good in compactness and obvious in hydrogen resistance effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material surface treatment, and in particular relates to a method for preparing a composite hydrogen barrier coating on the surface of zirconium hydride. Background Art

[0002] Zirconium hydride has high hydrogen density, low neutron capture cross section, negative temperature coefficient, high thermal stability, good thermal conductivity and processing performance, and is an ideal solid neutron moderator material. Nuclear reactor power sources using zirconium hydride as a moderator are gaining increasing attention because they provide long-term reliable energy with high power levels. However, zirconium hydride has the problem of hydrogen precipitation within the operating temperature range, which reduces the neutron moderation efficiency and service life.

[0003] Generally, a hydrogen barrier coating with a low hydrogen diffusion coefficient and a low surface recombination constant is prepared on the surface of zirconium hydride through surface treatment technology, which can prevent the precipitation of hydrogen in the zirconium hydride matrix and extend the service life of the zirconium hydride moderator.

[0004] At present, the main materials for hydrogen barrier coatings are oxides, carbides, nitrides, etc. On the surface of stainless steel or heat-resistant alloys, physical vapor deposition, chemical vapor deposition, spraying and other methods are often used to form hydrogen barrier coatings. Aluminum has a high affinity for oxygen, and aluminum oxide is very stable. Even under low oxygen partial pressure, it can resist hydrogen in reducing atmospheres such as CO, CO 2 and H 2 O can continue to oxidize, so the hydrogen permeability of aluminum oxide coatings often tends to continue to decrease during use.

[0005] The hydrogen barrier effect of the aluminide coating on the surface of zirconium hydride mainly comes from A1 2 O 3 However, A1 2 O 3 The distribution is uneven, the corrosion resistance life is limited, and aluminum is easily peeled off during wear, resulting in its actual hydrogen barrier effect is not ideal. An LDH coating with anti-corrosion effect can be prepared on the surface of the aluminum coating by an in-situ hydrothermal method, but the zinc-aluminum layered double hydroxide nanosheets of the coating cannot be stacked layer by layer, and they are loosely arranged, so the surface of the zinc-aluminum layered double hydroxide coating is not dense and has many pores, which affects the hydrogen barrier effect of the coating. Summary of the invention

[0006] In view of this, the technical solution disclosed in some embodiments is a method for preparing a composite hydrogen barrier coating on the surface of zirconium hydride, comprising the steps of:

[0007] S1. Spraying aluminum powder and aluminum oxide powder on the surface of the zirconium hydride substrate by low-pressure cold air spraying to form an aluminum coating; wherein the particle size of the aluminum powder is 35 to 45 μm, the particle size of the aluminum oxide powder is between 40 and 50 μm, and the purity of both is greater than 99%;

[0008] S2, aluminum coating on the surface of zirconium hydride substrate and Zn(NO 3 ) 2.6 H 2 O solution undergoes an in-situ hydrothermal reaction and in-situ growth forms a zinc-aluminum layered double hydroxide coating;

[0009] S3. The zinc-aluminum layered double hydroxide coating on the surface of the zirconium hydride substrate is compounded with graphene oxide by electrostatic adsorption to form a zinc-aluminum layered double hydroxide-graphene oxide composite hydrogen barrier coating on the surface of the zirconium hydride substrate.

[0010] Furthermore, some embodiments disclose a method for preparing a composite hydrogen barrier coating on the surface of zirconium hydride. In step S1, a low-pressure cold air spraying system is used to spray aluminum powder and aluminum oxide powder on the surface of the zirconium hydride substrate to form an aluminum coating, wherein the compressed air pressure is 0.4 to 0.8 MPa, the preheating temperature of the compressed air is 500 to 700°C, the spray gun movement speed is 150 to 300 mm / s, and the powder supply speed is 0.3 to 0.8 g / s.

[0011] In the method for preparing the composite hydrogen barrier coating on the surface of zirconium hydride disclosed in some embodiments, step S1 further comprises:

[0012] The aluminum coating on the surface of zirconium hydride is treated with alkaline solution to remove surface oxides.

[0013] In the preparation method of the composite hydrogen barrier coating on the surface of zirconium hydride disclosed in some embodiments, the alkali solution is a sodium hydroxide aqueous solution with a concentration of 2 to 6 mol / L, and the immersion treatment time in the sodium hydroxide aqueous solution is 100 to 150 seconds.

[0014] In some embodiments of the present invention, the method for preparing a composite hydrogen barrier coating on a zirconium hydride surface is disclosed, in step S2, Zn(NO 3 ) 2.6 H 2 The concentration of the O solution is 0.03-0.07 M, the in-situ hydrothermal reaction temperature is 75-100° C., and the reaction time is 12-36 h.

[0015] Some embodiments disclose a method for preparing a composite hydrogen barrier coating on the surface of zirconium hydride. In step S3, the zinc-aluminum layered double hydroxide coating on the surface of the zirconium hydride substrate is immersed in a graphene oxide sol. After immersion for 1 to 5 minutes, it is uniformly pulled out from the graphene oxide sol at a speed of 1 to 20 cm / min, and a zinc-aluminum layered double hydroxide-graphene oxide composite hydrogen barrier coating is formed on the surface of the zirconium hydride substrate; wherein the graphene oxide is made by the Hummers method, and the concentration of the graphene oxide sol is 0.1 to 0.5 mg / ml.

[0016] In the method for preparing the composite hydrogen barrier coating on the surface of zirconium hydride disclosed in some embodiments, step S3 also includes the step of drying the obtained zinc-aluminum layered double hydroxide-graphene oxide composite coating, and the drying temperature is 40 to 80°C.

[0017] In the method for preparing the composite hydrogen barrier coating on the surface of zirconium hydride disclosed in some embodiments, step S3 is repeated multiple times to obtain the zinc-aluminum layered double hydroxide-graphene oxide composite hydrogen barrier coating.

[0018] In the method for preparing the composite hydrogen barrier coating on the surface of zirconium hydride disclosed in some embodiments, step S3 is repeated 10 to 20 times to obtain the zinc-aluminum layered double hydroxide-graphene oxide composite hydrogen barrier coating.

[0019] In the method for preparing the composite hydrogen barrier coating on the surface of zirconium hydride disclosed in some embodiments, step S1 also includes a step of pretreating the zirconium hydride substrate.

[0020] The method for preparing a composite hydrogen barrier coating on the surface of a zirconium hydride substrate disclosed in an embodiment of the present invention uses electrostatic adsorption of graphene oxide to treat zinc-aluminum layered double hydroxide, and surface defects are repaired to obtain a zinc-aluminum layered double hydroxide-graphene oxide composite coating. The coating has good continuity, a complete and smooth surface, good density, and an obvious hydrogen barrier effect. It has good corrosion resistance and friction resistance, and can effectively extend the service life of the zirconium hydride moderator. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a flow chart of the method for preparing the composite hydrogen barrier coating on the surface of zirconium hydride disclosed in Example 1;

[0022] Figure 2 This is a schematic diagram of the structure of the composite hydrogen barrier coating on the surface of zirconium hydride disclosed in Example 1;

[0023] Figure 3 This is a morphology diagram of the composite hydrogen barrier coating on the surface of zirconium hydride disclosed in Example 1;

[0024] Figure 4 It is the hydrogen permeation reduction factor PRF of the composite hydrogen barrier coating on the surface of zirconium hydride disclosed in Example 1. DETAILED DESCRIPTION

[0025] The word "embodiment" used herein as an "exemplary" does not necessarily mean that any embodiment described is superior or better than other embodiments. Performance index tests in the embodiments of the present invention are performed using conventional test methods in the art unless otherwise specified. It should be understood that the terms described in the embodiments of the present invention are only used to describe specific implementation methods and are not intended to limit the contents disclosed in the embodiments of the present invention.

[0026] Unless otherwise specified, the technical and scientific terms used herein have the same meanings as commonly understood by ordinary technicians in the technical field to which the embodiments of the present invention belong; other experimental methods and technical means not specifically specified in the embodiments of the present invention refer to experimental methods and technical means commonly used by ordinary technicians in the field.

[0027] The terms "substantially" and "approximately" used herein are used to describe small fluctuations. For example, they can refer to less than or equal to ±5%, such as less than or equal to ±2%, such as less than or equal to ±1%, such as less than or equal to ±0.5%, such as less than or equal to ±0.2%, such as less than or equal to ±0.1%, such as less than or equal to ±0.05%. The numerical data represented or presented in the range format herein are used only for convenience and brevity, and should therefore be flexibly interpreted as including not only the values ​​clearly listed as the limits of the range, but also all independent values ​​or sub-ranges contained in the range. For example, the numerical range of "1-5%" should be interpreted as including not only the clearly listed values ​​of 1% to 5%, but also the independent values ​​and sub-ranges within the range shown. Therefore, independent values ​​such as 2%, 3.5% and 4% and sub-ranges such as 1%-3%, 2%-4% and 3%-5% are included in this numerical range. This principle also applies to the range of only one numerical value. In addition, such an interpretation applies regardless of the width of the range or the characteristics described.

[0028] In this document, including in the claims, transitional words such as "comprises," "includes," "with," "having," "containing," "involving," "accommodating," etc. are understood to be open-ended, i.e., meaning "including but not limited to." Only the transitional words "consisting of" and "composed of" are closed transitional words.

[0029] In order to better illustrate the present invention, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the gist of the present invention.

[0030] Under the premise of no conflict, the technical features disclosed in the embodiments of the present invention may be arbitrarily combined, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present invention.

[0031] In some embodiments, the method for preparing the composite hydrogen barrier coating on the surface of zirconium hydride comprises the steps of:

[0032] S101, pre-treating the zirconium hydride substrate; wherein the pre-treatment includes: grinding the surface of the zirconium hydride substrate step by step with SiC water sandpaper; then ultrasonically cleaning the zirconium hydride substrate in an acetone solution; and then cleaning with deionized water to remove the acetone solution remaining on the surface of the zirconium hydride substrate, and cleaning to obtain a clean zirconium oxide substrate;

[0033] S102. Aluminum powder and alumina powder are sprayed on the surface of zirconium hydride substrate by low-pressure cold air spraying system to form aluminum coating, wherein the mass ratio of aluminum powder to alumina powder is 3-4:1-2, the particle size of aluminum powder is 35-45 μm, the particle size of alumina powder is between 40-50 μm, the purity is greater than 99%, the compressed air pressure is 0.4-0.8 MPa, the preheating temperature of compressed air is 500-700°C, the movement speed of spray gun is 150-300 mm / s, and the powder supply speed is 0.3-0.8 g / s. Generally, ceramic particles are added to the metal substrate as reinforcements to improve the coating quality not only by reducing the porosity, but also by shot peening and roughening the coating to improve the adhesion strength and deposition efficiency. In addition, for low-pressure cold air spraying technology LPCGS, the ceramic phase is conducive to eliminating the accumulation of raw material powder in the nozzle and keeping the pipeline of the equipment powder transmission system unobstructed. The reinforcement can be made of SiC or Al 2 O 3 ;

[0034] S103, treating the aluminum coating on the surface of the zirconium hydride with an alkali solution to remove the surface oxides; wherein the alkali solution is a sodium hydroxide aqueous solution with a concentration of 2 to 6 mol / L, and the immersion treatment time in the sodium hydroxide aqueous solution is 100 to 150 seconds; generally, in order to better carry out the in-situ hydrothermal reaction in the subsequent process, the surface of the zirconium hydride sample is immersed in a low-concentration sodium hydroxide solution for a short time to remove the surface oxides without damaging the aluminum coating;

[0035] S104, aluminum coating on the surface of zirconium hydride substrate and Zn(NO 3 ) 2.6 H 2 O solution undergoes an in-situ hydrothermal reaction and in-situ growth forms a zinc-aluminum layered double hydroxide coating, namely, a ZnAl-LDH coating; wherein Zn(NO 3 ) 2.6 H 2 The concentration of the O solution is 0.03-0.07M, the in-situ hydrothermal reaction temperature is 75-100°C, and the reaction time is 12-36h; wherein, firstly in Zn(NO 3 ) 2.6 H 2 Ammonia water is added to the O solution to adjust the pH value of the solution to between 8 and 10, and then the aluminum coating on the surface of the zirconium hydride substrate is immersed in the solution for a hydrothermal reaction;

[0036] The hydrothermal reaction is:

[0037] Al(OH - ) 4 +[Zn(OH) 4 ] 2- +NO 3 - +H 2 O→ZnAl-LDHs;

[0038] S105, the zinc-aluminum layered double hydroxide coating on the surface of the zirconium hydride substrate is compounded with graphene oxide in an electrostatic adsorption manner to form a zinc-aluminum layered double hydroxide-graphene oxide composite hydrogen barrier coating on the surface of the zirconium hydride substrate; specifically comprising:

[0039] Graphene oxide is dispersed in an ethanol solution and ultrasonically stirred to obtain a graphene oxide sol;

[0040] The zinc-aluminum layered double hydroxide coating on the surface of the zirconium hydride substrate is immersed in a graphene oxide sol, and after being immersed for 1 to 5 minutes, it is uniformly pulled out from the graphene oxide sol at a speed of 1 to 20 cm / min, so that a zinc-aluminum layered double hydroxide-graphene oxide composite hydrogen barrier coating is formed on the surface of the zirconium hydride substrate; wherein the graphene oxide is prepared by a Hummers method, and the concentration of the graphene oxide sol is 0.1 to 0.5 mg / ml;

[0041] S106, a step of drying the obtained zinc-aluminum layered double hydroxide-graphene oxide composite coating, wherein the drying temperature is 40 to 80° C.;

[0042] S107, steps S105 and S106 are repeated 10 to 20 times to obtain a zinc-aluminum layered double hydroxide-graphene oxide composite hydrogen barrier coating.

[0043] The technical details are further illustrated below in conjunction with embodiments.

[0044] Example 1

[0045] like Figure 1 As shown, the method for preparing the composite hydrogen barrier coating on the surface of zirconium hydride disclosed in Example 1 includes:

[0046] ZrH 1.8 The raw material was cut into Φ10mm×2mm thin slices of zirconium hydride samples as the zirconium oxide matrix; the surface and corners of the zirconium hydride samples were mechanically polished step by step with 360#, 600#, and 800# SiC water sandpaper respectively; the samples were ultrasonically cleaned in acetone solution for 10 minutes, and then washed with deionized water to remove the residual acetone solution on the surface of the samples, and then sandblasted after drying to make the surface rough;

[0047] Ultrasonic cleaning and drying of aluminum powder and aluminum oxide powder;

[0048] A commercial cold spray system is used to spray aluminum powder and aluminum oxide powder on the surface of the treated zirconium hydride sample by low-pressure cold air spraying to form an aluminum coating; during low-pressure cold air spraying, 0.4Mpa compressed air is preheated to 500°C, the spray gun moves at a speed of 150mm / s, and the powder supply speed is 0.3g / s; the commercial cold spray system can use the LPCS system DYMET 423 of the Russian OCPS company;

[0049] The zirconium hydride sample treated by low-pressure cold air spraying was immersed in a 2 mol / L NaOH aqueous solution for 150 s to remove the surface oxides;

[0050] At a concentration of 0.03 M Zn(NO 3 ) 2.6 H 2 Ammonia water is added to the O solution to adjust the pH value to 8 to obtain a hydrothermal reaction solution; the treated sample is placed in the hydrothermal reaction solution, and an in-situ hydrothermal reaction is carried out at 75° C. for 36 hours to obtain a zinc-aluminum layered double hydroxide coating, namely, a ZnAl-LDH coating;

[0051] The zirconium hydride sample with ZnAl-LDH coating was immersed in 0.1 mg / ml graphene oxide sol for electrostatic adsorption; after immersion for 5 min, the zirconium hydride sample was uniformly pulled out from the graphene oxide sol at a speed of 5 cm / min and dried at 40°C for 60 s;

[0052] The above-mentioned immersion and drying process was repeated 20 times to obtain a complete zinc-aluminum layered double hydroxide-graphene oxide composite coating.

[0053] The zinc-aluminum layered double hydroxide coating obtained in Example 1 was analyzed using a scanning electron microscope. Figure 2 As shown, it can be clearly seen that the zinc-aluminum layered double hydroxide nanoplates grow roughly vertically on the substrate, with uniform and dense distribution; the cross-section of the zinc-aluminum layered double hydroxide-graphene oxide composite coating was analyzed using a scanning electron microscope, and the results showed that the thickness of the obtained hydrogen barrier coating was about 20μm; the hydrogen permeation reduction factor PRF was used to quantitatively characterize the hydrogen barrier performance of the oxide film on the surface of zirconium hydride, and the results are shown in Figure 3 As shown, the maximum PRF value of the zinc-aluminum layered double hydroxide-graphene oxide composite coating is 24.8, and the composite hydrogen barrier coating has a good hydrogen barrier effect.

[0054] Example 2

[0055] The method for preparing the composite hydrogen barrier coating on the surface of zirconium hydride disclosed in Example 2 comprises:

[0056] ZrH 1.8 The raw material was cut into Φ10mm×2mm thin slices of zirconium hydride samples as the zirconium oxide matrix; the surface and corners of the zirconium hydride samples were mechanically polished step by step with 360#, 600#, and 800# SiC water sandpaper respectively; the samples were ultrasonically cleaned in acetone solution for 5 minutes, and then washed with deionized water to remove the residual acetone solution on the surface of the sample, and then sandblasted after drying to make the surface rough;

[0057] Ultrasonic cleaning and drying of aluminum powder and aluminum oxide powder;

[0058] A commercial cold spray system was used to spray aluminum powder and aluminum oxide powder on the surface of the treated zirconium hydride sample by low-pressure cold air spraying to form an aluminum coating. During low-pressure cold air spraying, 0.6Mpa compressed air was preheated to 600°C, the spray gun moved at a speed of 200mm / s, and the powder supply speed was 0.5g / s.

[0059] The zirconium hydride sample treated by low-pressure cold air spraying was immersed in a 4 mol / L NaOH aqueous solution for 90 seconds to remove the surface oxides;

[0060] At a concentration of 0.05 M Zn(NO 3 ) 2.6 H 2 Ammonia water is added to the O solution to adjust the pH value to 9 to obtain a hydrothermal reaction solution; the treated sample is placed in the hydrothermal reaction solution, and an in-situ hydrothermal reaction is carried out at 85° C. for 24 hours to obtain a zinc-aluminum layered double hydroxide coating, namely, a ZnAl-LDH coating;

[0061] The zirconium hydride sample with ZnAl-LDH coating was immersed in 0.3 mg / ml graphene oxide sol for electrostatic adsorption; after immersion for 3 min, the zirconium hydride sample was uniformly pulled out from the graphene oxide sol at a speed of 10 cm / min and dried at 60°C for 40 s;

[0062] The above-mentioned immersion and drying process was repeated 15 times to obtain a complete zinc-aluminum layered double hydroxide-graphene oxide composite coating.

[0063] The zinc-aluminum layered double hydroxide coating obtained in Example 2 was analyzed using a scanning electron microscope, and it can be clearly seen that the zinc-aluminum layered double hydroxide nanoplates grow roughly vertically on the substrate, and are evenly distributed and dense; the cross-section of the zinc-aluminum layered double hydroxide-graphene oxide composite coating was analyzed using a scanning electron microscope, and the results showed that the thickness of the obtained hydrogen barrier coating was about 30 μm; the hydrogen permeation reduction factor PRF was selected to quantitatively characterize the hydrogen barrier properties of the zirconium hydride surface oxide film, and the results showed that the maximum PRF value of the zinc-aluminum layered double hydroxide-graphene oxide composite coating was 25.3, and the hydrogen barrier effect of the composite hydrogen barrier coating was good.

[0064] Example 3

[0065] The method for preparing the composite hydrogen barrier coating on the surface of zirconium hydride disclosed in Example 3 comprises:

[0066] ZrH 1.8 The raw material was cut into Φ10mm×2mm thin slices of zirconium hydride samples as the zirconium oxide matrix; the surface and corners of the zirconium hydride samples were mechanically polished step by step with 360#, 600#, and 800# SiC water sandpaper respectively; the samples were ultrasonically cleaned in acetone solution for 15 minutes, and then washed with deionized water to remove the residual acetone solution on the surface of the samples, and then sandblasted after drying to make the surface rough;

[0067] Ultrasonic cleaning and drying of aluminum powder and aluminum oxide powder;

[0068] A commercial cold spray system was used to spray aluminum powder and aluminum oxide powder on the surface of the treated zirconium hydride sample by low-pressure cold air spraying to form an aluminum coating. During low-pressure cold air spraying, 0.8Mpa compressed air was preheated to 700°C, the spray gun moved at a speed of 300mm / s, and the powder supply speed was 0.8g / s.

[0069] The zirconium hydride sample treated by low-pressure cold air spraying was immersed in a 6 mol / L NaOH aqueous solution for 60 seconds to remove the surface oxides;

[0070] At a concentration of 0.07 M Zn(NO 3 ) 2.6 H 2 Ammonia water is added to the O solution to adjust the pH value to 10 to obtain a hydrothermal reaction solution; the treated sample is placed in the hydrothermal reaction solution, and an in-situ hydrothermal reaction is carried out at 100° C. for 12 hours to obtain a zinc-aluminum layered double hydroxide coating, namely, a ZnAl-LDH coating;

[0071] The zirconium hydride sample with ZnAl-LDH coating was immersed in 0.5 mg / ml graphene oxide sol for electrostatic adsorption; after immersion for 1 min, the zirconium hydride sample was uniformly pulled out from the graphene oxide sol at a speed of 8 cm / min and dried at 80°C for 40 s;

[0072] The above-mentioned immersion and drying process was repeated 10 times to obtain a complete zinc-aluminum layered double hydroxide-graphene oxide composite coating.

[0073] The zinc-aluminum layered double hydroxide coating obtained in Example 3 was analyzed using a scanning electron microscope, and it can be clearly seen that the zinc-aluminum layered double hydroxide nanoplates grow roughly vertically on the substrate, and are evenly distributed and dense; the cross-section of the zinc-aluminum layered double hydroxide-graphene oxide composite coating was analyzed using a scanning electron microscope, and the results showed that the thickness of the obtained hydrogen barrier coating was about 50 μm; the hydrogen permeation reduction factor PRF was selected to quantitatively characterize the hydrogen barrier properties of the zirconium hydride surface oxide film, and the results showed that the maximum PRF value of the zinc-aluminum layered double hydroxide-graphene oxide composite coating was 26.4, and the hydrogen barrier effect of the composite hydrogen barrier coating was good.

[0074] The method for preparing a composite hydrogen barrier coating on the surface of a zirconium hydride substrate disclosed in an embodiment of the present invention uses electrostatic adsorption of graphene oxide to treat zinc-aluminum layered double hydroxide, and surface defects are repaired to obtain a zinc-aluminum layered double hydroxide-graphene oxide composite coating. The coating has good continuity, a complete and smooth surface, good density, and an obvious hydrogen barrier effect. It has good corrosion resistance and friction resistance, and can effectively extend the service life of the zirconium hydride moderator.

[0075] The technical solutions disclosed in the embodiments of the present invention and the technical details disclosed in the embodiments are merely illustrative of the inventive concept of the present invention and do not constitute a limitation on the technical solutions of the embodiments of the present invention. Any conventional changes, replacements or combinations of the technical details disclosed in the embodiments of the present invention have the same inventive concept as the present invention and are within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a composite hydrogen barrier coating on the surface of zirconium hydride, characterized in that: Includes steps: S1. Spraying aluminum powder and aluminum oxide powder on the surface of the zirconium hydride substrate by low-pressure cold air spraying to form an aluminum coating; wherein the particle size of the aluminum powder is 35 to 45 μm, the particle size of the aluminum oxide powder is between 40 and 50 μm, and the purity of both is greater than 99%; S2, aluminum coating on the surface of zirconium hydride substrate and Zn(NO3) 2.6 The H2O solution undergoes an in-situ hydrothermal reaction and in-situ growth forms a zinc-aluminum layered double hydroxide coating; S3. The zinc-aluminum layered double hydroxide coating on the surface of the zirconium hydride substrate is compounded with graphene oxide by electrostatic adsorption to form a zinc-aluminum layered double hydroxide-graphene oxide composite hydrogen barrier coating on the surface of the zirconium hydride substrate.

2. The method for preparing the composite hydrogen barrier coating on the surface of zirconium hydride according to claim 1, characterized in that: In step S1, aluminum powder and aluminum oxide powder are sprayed on the surface of the zirconium hydride substrate using a low-pressure cold air spray system to form an aluminum coating, wherein the compressed air pressure is 0.4-0.8 MPa, the preheating temperature of the compressed air is 500-700°C, the spray gun moving speed is 150-300 mm / s, and the powder supply speed is 0.3-0.8 g / s.

3. The method for preparing the composite hydrogen barrier coating on the surface of zirconium hydride according to claim 1, characterized in that: Step S1 also includes: The aluminum coating on the surface of zirconium hydride is treated with alkaline solution to remove surface oxides.

4. The method for preparing the composite hydrogen barrier coating on the surface of zirconium hydride according to claim 3, characterized in that: The alkali solution is a sodium hydroxide aqueous solution with a concentration of 2 to 6 mol / L, and the soaking time in the sodium hydroxide aqueous solution is 100 to 150 seconds.

5. The method for preparing the composite hydrogen barrier coating on the surface of zirconium hydride according to claim 1, characterized in that: In step S2, Zn(NO3) 2.6 The concentration of the H2O solution is 0.03-0.07M, the in-situ hydrothermal reaction temperature is 75-100°C, and the reaction time is 12-36h.

6. The method for preparing the composite hydrogen barrier coating on the surface of zirconium hydride according to claim 1, characterized in that: In step S3, the zinc-aluminum layered double hydroxide coating on the surface of the zirconium hydride substrate is immersed in the graphene oxide sol. After immersion for 1 to 5 minutes, it is uniformly pulled out from the graphene oxide sol at a speed of 1 to 20 cm / min to form a zinc-aluminum layered double hydroxide-graphene oxide composite hydrogen barrier coating on the surface of the zirconium hydride substrate; wherein the graphene oxide is made by the Hummers method, and the concentration of the graphene oxide sol is 0.1 to 0.5 mg / ml.

7. The method for preparing the composite hydrogen barrier coating on the surface of zirconium hydride according to claim 6, characterized in that: Step S3 also includes the step of drying the obtained zinc-aluminum layered double hydroxide-graphene oxide composite coating, and the drying temperature is 40 to 80°C.

8. The method for preparing the composite hydrogen barrier coating on the surface of zirconium hydride according to claim 7, characterized in that: Step S3 is repeated multiple times to obtain a zinc-aluminum layered double hydroxide-graphene oxide composite hydrogen barrier coating.

9. The method for preparing a composite hydrogen barrier coating on the surface of zirconium hydride according to claim 8, characterized in that: Step S3 is repeated 10 to 20 times to obtain a zinc-aluminum layered double hydroxide-graphene oxide composite hydrogen barrier coating.

10. The method for preparing the composite hydrogen barrier coating on the surface of zirconium hydride according to claim 1, characterized in that Step S1 also includes the step of pretreating the zirconium hydride substrate.